Determinacion de zonas potenciales para cultivos frutícolas en la región Tacna, mediante sistemas de análisis espacial - Alva Huayaney, Miguel Ernesto (2013)
The Agro-Ecological Zonation (ZAE) defines areas based on soil, physiography and climatic characteristic combinations (FAO, 1997). To do this, the Geographic Information Systems (GIS) by using the Help Systems for Spatial Decision (SADE) are a tool of fundamental importance in topics related to the agrarian development. This allows us to manage the variables of the physical environment where this activity is made, such as the climate, soil, and water; each one is characterized by the spatial variation of the territory. Climate is mainly influenced by the place topography; soil is considered as a potential resource but also as a hindrance to the cultigens’ growth; water is considered as one of the main shortages for the Tacna Region, and its influence on crops is analyzed according to its availability and quality. All these variables should be spatialized within the study area to integrate them in function to its degree influence to the wealthy growth of crops, especially at present where there are very favorable conditions to the Region. This condition is accentuated because our country has Free Trade Agreements with several countries that are potential markets for some fruit.The second part of the project covers the modeling in GIS to evaluate potentials and limitations of the main crops of the region for export: cantaloupe, water melon and other cucurbitaceous, oregano and onion of the Region Tacna (Agro-Ecological Zonation). This consists on the formulation of four sub models: physical-geographical, climatic, agro-ecologic and hydric,which are next integrated to formulate the Agro-Ecological Zoning (ZAE).